Heidegger in France - Janicaud, Dominique, 1937- (Studies in Continental thought., 2015)
Dominique Janicaud claimed that every French intellectual movement'from existentialism to psychoanalysis'was influenced by Martin Heidegger. This translation of Janicaud's landmark work, Heidegger en France, details Heidegger's reception in philosophy and other humanistic and social science disciplines. Interviews with key French thinkers such as Francoise Dastur, Jacques Derrida, Eliane Escoubas, Jean Greisch, Philippe Lacoue-Labarthe, Jean-Luc Marion, and Jean-Luc Nancy are included and provide further reflection on Heidegger's relationship to French philosophy. An intellectual undertaking of authoritative scope, this work furnishes a thorough history of the French reception of Heidegger's thought.